Analisa Yuridis Efektivitas Perlindungan Investor dalam Transaksi Repurchase Agreement (Repo) di Indonesia - Yudhi Priyo Amboro; Yuly Milyarti Wijaya (Fakultas Hukum, Universitas Internasional Batam, 2017)
In the capital market, securities companies have the role of the intermediary for security traders, which may conduct business activity of selling and purchasing securities such as shares and bonds. Repurchase Agreement (Repo) transaction is one of the investment products of the Securities Companies which is based on the sell or purchase of securities contract with the sellback or buyback condition at the determined period. The prevailing agreement principle is the freedom of contract so that it would be very much dependent on the provisions being stipulated in the Repurchase Agreement made by the relevant parties.This research shall clearly describe on the illustration of the securities transaction at the Capital market in Indonesia and the Law and Regulations which regulate on the Repo Transaction in Indonesia. This research is a juridical normative research using method of researching library materials. Thus, the source of data being used shall be in the form of secondary data gathered with literature review technique. Upon gathering of all the data, then such data were being processed and analized with the qualitative descriptive analizing method, namely by grouping the data in accordance to the researched aspects which thereafter the conclusion can be taken and shall be elaborated descriptively. Based on this research, it was resulted that regulation which govern the Repo Transaction is stipulated in the Otoritas Jasa Keuangan Regulation Number 9/Pojk.04/2015 Regarding Transaction Guidelines on Repurchase Agreement for Financial Services Institution. However, if being reviewed by the legal protection and legal effecitivity theory, such regulation is still less effective.